2022
DOI: 10.1620/tjem.2022.j078
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Whole-Brain Low-Intensity Pulsed Ultrasound Therapy for Early Stage of Alzheimer’s Disease (LIPUS-AD): A Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: A pilot study of whole-brain low-intensity pulsed ultrasound therapy for early stage of Alzheimer's disease (LIPUS-AD): A randomized, doubleblind, placebo-controlled trial

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…1. In the clinical trial, we designed to produce sound pressure of 0.15 to 0.19 MPa in the deepest part of the hippocampus (approximately 8 cm deep), and sound pressure just below the skull needed to be 1.0 to 1.5 MPa or less to ensure safety 10 . The cone angle of the diffusive probe was set according to the size of the average elderly Japanese skull.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1. In the clinical trial, we designed to produce sound pressure of 0.15 to 0.19 MPa in the deepest part of the hippocampus (approximately 8 cm deep), and sound pressure just below the skull needed to be 1.0 to 1.5 MPa or less to ensure safety 10 . The cone angle of the diffusive probe was set according to the size of the average elderly Japanese skull.…”
Section: Discussionmentioning
confidence: 99%
“…The LIPUS therapy was performed for a total of 6 sessions 10 . Among the 22 patients divided into 2 group in a 1:1 fashion, cognitive functions remained unchanged in the LIPUS group, while they progressively worsened at 24, 48, and 72 weeks in the placebo group 10 . Furthermore, no adverse effects were noted 10 .…”
Section: Introductionmentioning
confidence: 99%
“…We also have demonstrated the effectiveness of "whole-brain" irradiation of the LIPUS therapy in mouse models of cerebrovascular dementia [22], cerebral infarction [23], and Alzheimer's disease [22], where eNOS plays a pivotal role. Moreover, we have recently conducted a randomized, double-blind, placebo-controlled pilot trial of the LIPUS therapy for early stage of Alzheimer's disease [24]. We found that the LIPUS therapy tended to suppress cognitive impairment at 24, 48, and 72 weeks as compared with the placebo group [24].…”
Section: Plos Onementioning
confidence: 94%
“…The major problem with the current clinical data concerns a lack of sham-controlled trials. Only 3 studies included a sham control, [33,37,41] with 2 of them reporting a significant clinical benefit for verum over sham. [33,37] Although there is clear independent evidence from neurophysiological techniques that ultrasound generates local neuromodulation in patients (see above) and healthy individuals (compare Sarica et al [46] ) and recently the first study showing true more than sham fMRI effects in humans appeared, [48] it is yet unknown to what extent changed neuronal activity translates into clinical effects.…”
Section: Safety Of Clinical Ultrasound Neuromodulationmentioning
confidence: 99%
“…The major problem with the current clinical data concerns a lack of sham‐controlled trials. Only 3 studies included a sham control, [ 33 , 37 , 41 ] with 2 of them reporting a significant clinical benefit for verum over sham. [ 33 , 37 ] Although there is clear independent evidence from neurophysiological techniques that ultrasound generates local neuromodulation in patients (see above) and healthy individuals (compare Sarica et al.…”
Section: Perspectives For Ultrasound Neuromodulation As a New Brain T...mentioning
confidence: 99%